Measurement of Glomerular Filtration Rate Using Multiphasic Computed Tomography in Patients With Unilateral Renal Tumors: A Feasibility Study - Wang, Tingting; Xu, Yi; Liu, Wangyan; Shao, Pengfei; Lv, Qiang; Yang, Guanyu; Tang, Lijun (Frontiers in Physiology, 2019)
Objectives: This study was to assess the feasibility of a modified multiphasic CT scan protocol combined with homemade software measurements of glomerular filtration rate (CT-GFR) and explore the effect of renal tumor volume on the calculation of CT-GFR. Materials and Methods: Prospective observational study comparing three methods of GFR measurement from February 2017 to December 2017, ninety-one patients with unilateral renal tumor underwent both a modified multiphasic CT scans of kidney and serum creatinine tests preoperatively, of which 15 cases underwent additional radionuclide examination. Total and split CT-GFR, with or without renal tumor, were quantified by the homemade software in early and late renal parenchymal phases respectively. The volume of renal tumor was quantified by the homemade software. Correlation and difference between CT-GFR and traditional methods of GFR measurement, including estimated GFR (eGFR) from serum creatinine concentration and split GFR using of radionuclide examination (R-GFR), were performed. Results: There is a strong correlation between CT-GFR with renal tumor and eGFR (r=0.90, p<0.001) in early renal parenchymal phase. The relative CT-GFR in early renal parenchymal phase were highly correlated with the relative R-GFR (r=0.88, p<0.001). Renal tumor volume significantly correlated with the value of CT-GFR that determined by subtracting the CT-GFR measurement without renal tumor from CT-GFR measurement with renal tumor (r=0.89, p<0.001). Conclusion: A modified multiphasic CT scan protocol combined with homemade software might be an alternative technique for the evaluation of renal function for the patients with unilateral renal tumor.